Analisis Aspek Finansial dalam Perencanaan Unit Pengolahan Keju Mozzarella: Analysis of Financial Aspects in Planning a Mozzarella Cheese Processing Unit - Alqowi Yanuarsyah, Aula; Hermanuadi, Didiek (JOFE : Journal of Food Engineering, 2024)
Mozzarella cheese is semi-matured cheese made from cow or buffalo milk. Mozzarella cheese has a soft, stringy and elastic texture. The aim of this research is to find a mozzarella cheese processing facility design and determine how feasible it is to set up a mozzarella cheese business. The standing location unit is located in Malang Regency, this location unit has a room area of ​​271.30 m2 and a total area of ​​2,357.5 m2. Has a production capacity of 3 tons per day, production cycle produces 469.47 kg, and 8 working hours per day. The results of the financial aspect analysis show that the NPV is IDR 2,063,253,246, B/C Ratio 1.1, IRR 66%, and PBP for 2 years. Based on these results, the establishment of a mozzarella cheese processing unit with a capacity of 3 tons per day is feasible because the financial feasibility criteria are met.